Comparing health care system and physician practice influences on social risk screening. Issue 1 (5th January 2022) - Frehn, Jennifer L.; Brewster, Amanda L.; Shortell, Stephen M.; Rodriguez, Hector P.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Health care systems can support dissemination of innovations, such as social risk screening in physician practices, but to date, no studies have examined the association of health system characteristics and practice-level adoption of social risk screening. Purpose: The aim of the study was to examine the association of multilevel organizational capabilities and adoption of social risk screening among system-owned physician practices. Methodology: Secondary analyses of the 2018 National Survey of Healthcare Organizations and Systems were conducted. Multilevel linear regression models examined physician practice and system characteristics associated with practice adoption of screening for five social risks (food insecurity, housing instability, utility needs, interpersonal violence, and transportation needs), accounting for clustering of practices within systems using random effects. Results: System-owned practices screened for an average of 1.7 of the five social risks assessed. The intraclass correlation indicated 16% of practice variation in social risk screening was attributable to differences between their health systems owners, with 84% attributable to differences between individual practices. Practices owned by systems with multiple hospitals screened for an additional 0.44 social risks ( p = .046) relative to practices of systems without hospitals. Practice characteristics associated with social risk screening included health information technology capacity (β = 0.20, p = .005), innovation culture (β = 0.26, p < .001), and patient engagement strategies (β = 0.57, p < .001). Conclusions: Health care system capabilities account for less variation in physician practice adoption of social risk screening compared to practice-level capabilities. Practice Implications: Efforts to expand social risk screening among system-owned physician practices should focus on supporting practice capabilities, including enhancing health information technology, promoting an innovative organizational culture, and advancing patient engagement strategies.